The prevalence of pulmonary embolism in patients with COVID-19 and respiratory decline: A three-setting comparison (2020)
Background The risk of pulmonary embolism (PE) in patients with Coronavirus Disease 2019 (COVID-19) is recognized. The prevalence of PE in patients with respiratory deterioration at the Emergency Department (ED), the regular ward, and the Intensive Care Unit (ICU) are not well-established. Objectives We aimed to investigate how often PE was present in individuals with COVID-19 and respiratory deterioration in different settings, and whether or not disease severity as measured by CT-severity score (CTSS) was related to the occurrence of PE. Patients/Methods Between April 6th and May 3rd, we enrolled 60 consecutive adult patients with confirmed COVID-19 from the ED, regular ward and ICU who met the pre-specified criteria for respiratory deterioration. Results A total of 24 (24/60: 40% (95%CI: 28-54%)) patients were diagnosed with PE, of whom 6 were in the ED (6/23: 26% (95% CI: 10-46%)), 8 in the regular ward (8/24: 33% (95%CI: 16-55%)), and 10 in the ICU (10/13: 77% (95%CI: 46-95%)). CTSS (per unit) was not associated with the occurrence of PE (age and sex-adjusted OR 1.06 (95%CI 0.98-1.15)). Conclusion The number of PE diagnosis among patients with COVID-19 and respiratory deterioration was high; 26% in the ED, 33% in the regular ward and 77% in the ICU respectively. In our cohort CTSS was not associated with the occurrence of PE. Based on the high number of patients diagnosed with PE among those scanned we recommend a low threshold for performing computed tomography angiography in patients with COVID-19 and respiratory deterioration.